Pengaruh Kesadaran Wajib Pajak, Tingkat Kepercayaan Terhadap Pemerintah, Sanksi Perpajakan Dan Implementasi Penerapan E-Samsat Terhadap Kepatuhan Perpajakan: (Studi Kasus Wajib Pajak Kendaraan Bermotor Di Wilayah Jakarta Selatan) - Sitanggang, Grace Deoni; Budyastuti, Triyani (Jurnal EMT KITA, 2024)
The increasing number of vehicles in Jakarta and the efforts of the tax authorities to develop innovations that make life easier for taxpayers should be in line with the amount of tax revenue. However, the increase in cases of misuse of taxpayers' money has led to a decline in public trust in the tax authorities. This study aims to examine the influence of taxpayer awareness, trust in government, tax sanctions, and the implementation of e-Samsat on the compliance of motor vehicle taxpayers in South Jakarta. This research uses a non-probability sampling technique with a purposive sampling approach. The sample consists of 100 respondents out of 273 respondents. The sample criteria for this study are taxpayers registered with South Jakarta Samsat. The data collection technique is a questionnaire. The scale used in this research is the Likert scale. The data analysis technique used is SMARTPLS 3. The results of this study indicate that taxpayer awareness, trust in the government, tax sanctions, and the implementation of e-Samsat have a positive and significant effect on motor vehicle taxpayer compliance.